Internationalization and Global Exchange: : The California State University, Stanislaus and PUC Minas’ Partnership - Ramos-Sollai, Sílvia; Alvim, Renato (Conecte-se! Revista Interdisciplinar de Extensão, 2024)
ABSTRACT This study is part of a larger research work that analyzes two projects including university students to exchange information about their academic experience. The projects are read as promotional of equity-minded education and part of the process of internationalization at California State University, Stanislaus. Initially motivated by the challenges imposed by the COVID-19 pandemic, the first project targeted Portuguese language students from two different US institutions to practice Portuguese due to the of the cost of mobility for study abroad programs and a recent culture of being an exchange student. The transition from face to face to online instruction amid the COVID-19 outbreak scenario posed various difficulties to Portuguese World Language teaching and learning. Syllabi were discontinued as everyone's knowledge, information, and communication technology literacy skills were challenged. One of the most affected class components was the interpersonal mode of communication. Shouldering the goal of promoting authentic oral practice, we piloted, examined, and analyzed meaning negotiation during conversational interactions. To investigate this uncharted area, we were led by the overarching question: what events, attitudes, beliefs, and policies shape remote interpersonal communication in internationalization and global exchange? The supporting question was: how do participants perceive meaning negotiation during conversations in the target language? Results pointed to a positive impact on students achieved by optimized talk time, higher volume of meaning negotiation, and increased time of information exchange due to the target language span time-module learning objectives ratio.